THE IMPLEMENTATION OF VOCABULARY STUDY TECHNIQUE ON STUDENTS’ READING COMPETENCY IN CLASS VIIIE AT SMPN 3 SINGARAJA IN THE ACADEMIC YEAR 2015/2016 - ., Ida Ayu Fajar Librayanti; ., Prof. Dr. Dewa Komang Tantra,Dip.,App.; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mengetahui jumlah siswa yang dikategorikan bermasalah dalam kompetensi membaca dengan menerapkan Teknik Pelajaran Kosa Kata pada kelas VIIIE SMPN 3 Singaraja Tahun ajaran 2015/2016. Ada beberapa langkah yang digunakan pada teknik Pelajaran Kosa Kata. Diantaranya 1) bunyi dan makna 2) pengulangan 3)penulisan isi 4)kalimat pembantu. Untuk mencapai tujuan, peneliti menggunakan penelitian tindakan kelas (PTK). Subjek dari penelitian ini adalah siswa dari kelas VIIIE SMPN 3 Singaraja. Dalam penelitian ini, peneliti menggunakan beberapa instrumen untuk pengumpulan data. 1) test 2) catatan peneliti 3) kuisioner. Data diperoleh dari hasil analisis mengguakan metode kualitatif dan kuantitatif. Hasil dari penelitian ini menunjukkan bahwa penerapan pelajaran kosa kata telah mengurangi jumlah siswa yang dikategorikan bermasalah dalam kemampuan membaca dari kelas VIIIE SMPN 3 Singaraja pada tahun ajaran 2015/2016. Pertama, berdasarkan kemampuan membaca siswa secara umum; kedua, kemampuan membaca siswa berdasarkan jenis teks; dan yang ketiga, kemampuan membaca siswa berdasakan indikator. Jumlah siswa yang bermasalah dalam kompetensi membaca berdasarkan kemampuan siswa secara umum, ada 30(88%) siswa dari 34 siswa pada test observasi awal; pada siklus I mengalami penurunan menjadi 10(33.33%) siswa; dan pada siklus terakhir ada 3(8.79%) siswa yang mengalami masalah dalam kompetensi membaca. 3 orang siswa yang pada siklus terakhir tidak mampu mencapai ketuntasan minimal (75) karena kurangnya motivasi dan terbatas dalam kosa kata.Berdasarkan catatan peneliti, penerapan pelajaran kosa kata mampu memotivasi siswa dalam mengikuti kelas membaca. Dalam kuisioner siswa juga memberi respon positif kepada pelaksanaan pelajaran kosa kata tersebut. Kata Kunci : Kompeteni membaca, Teknik Pelajaran Kosa Kata This research was aimed at finding out the decreasing number of students had problem in reading competency by implementing Vocabulary Study Technique of class VIIIE at SMPN 3 Singaraja in academic year 2015/2016. There were some steps that can be used in Vocabulary Study Technique. There are 1) sound and meaning, 2) repetition, 3) written form, and 4) illustrative sentence. To achieve the goal, the researcher used action based research. The subjects of this research were the students of class VIIIE at SMPN 3 Singaraja. In this research, the researcher used some instruments to collect the data. 1) test 2) researcher diary 3) questionnaire. The data obtained from the test were analyzed by using descriptive and quantitative method. The data obtained from the researcher diary and the questionnaires were analyzed by using qualitative method. The result of this research showed that the implementation of Vocabulary Study Technique could decrease number of students had problem in reading competency of class VIIIE at SMPN 3 Singaraja in academic year 2015/2016.First, based on general reading competency; second, based on the students’ reading competency based on the text type; and the last, based on the students’ reading competency based on its indicators. The total number of students had problem in reading competency based on general reading competency, there were 30(88%) students from 34 students in preliminary observation test; while in cycle I was decreased become 10(33.33%) students; then in the last cycle there were 3(8.79%) students still had problem in reading competency. The 3 students in cycle II, they couldn’t pass the performance indicators (75) because they lack of motivation in reading and lack of vocabulary. Based on researcher’s diary, the implementation of Vocabulary Study Technique could motivate them to follow the reading class. On the questionnaire the students also gave the positive response to the implementation of Vocabulary Study Technique. keyword : reading competency, vocabulary study technique